The Knowledge And Practice Of Copy Denture Technique Among Dentist And Dental Technologist - Norlela Yacob; Faizah Abdul Fatah; Wan Nor Syariza Wan Ali; Nusima Mohamed; Tine Martina Winarti; Aida Ali (International Islamic University Malaysia, 2024)
Introduction: Copy denture technique is a classic technique for construction of a new denture based on the favourable aspects of the original denture using a replica. This technique helps in adaptation of new denture in elderly population. The aim of this paper was to assess the knowledge and practice of copy denture technique among dentists and dental technologists. Materials and Methods: A pre-tested questionnaire was sent to all participants who attended the Copy Denture Workshop organized by USIM on 13th April 2017. Two sets of the same questionnaire were distributed to the participant before and after the seminar. Results: Out of 100 participants, only 77% (n=77) have given valid feedbacks. The results showed, even though 54.5% (n=42) participants had more than 5 years of clinical experience, 42.9% (n=33) of the participants have poor knowledge in this technique before the seminar begin. However 55.9% presented with positive attitude towards copy denture. Most of the participants did not know about copy denture technique (43.1%) and the advantages of the technique (32.9%). 74.1% (n=57) participants were uncertain to perform the technique and did not have the skills to perform the copy denture technique. However, after attending the workshop, their attitude towards copy denture increased (+15.6%) and the mean score value was statistically significance with p-value 0.049. Conclusion(s): Awareness and workshop on copy denture technique should be encouraged to improve knowledge and practice, so that the patient who requested for replacement denture will benefit from this technique.